2016
DOI: 10.1111/petr.12728
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1 receptor antibodies in childhood kidney transplantation

Abstract: Angiotensin II type 1 receptor antibodies (AT 1 RAb) have emerged as non-HLA Ab present in patients with acute AMR and risk of graft loss. Furthermore, AT 1 RAb have been shown to increase angiotensin II sensitivity which may play a role in the development of CVD and hypertension. Data on AT 1 RAb in stable transplant recipients are lacking. The aim of this study was to analyze the levels of AT 1 RAb in a cohort of stable patients after kidney transplantation (tx) in childhood. A cross-sectional study of 30 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…We and others have described that AT1R-Ab levels are higher in pediatric kidney transplant recipients when compared with adults. 33,35 Given AT1R-Ab and ETAR-Ab are highly correlated, 23 it is not surprising that we found a higher level to be more informative in our population. In an analysis of adult kidney transplant recipients with similar serial sampling, only 4% of blood samples were positive for ETAR-Ab (vs. 22% in our cohort) and only 56% of these samples were also positive for AT1R-Ab (vs. 96% in our cohort).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We and others have described that AT1R-Ab levels are higher in pediatric kidney transplant recipients when compared with adults. 33,35 Given AT1R-Ab and ETAR-Ab are highly correlated, 23 it is not surprising that we found a higher level to be more informative in our population. In an analysis of adult kidney transplant recipients with similar serial sampling, only 4% of blood samples were positive for ETAR-Ab (vs. 22% in our cohort) and only 56% of these samples were also positive for AT1R-Ab (vs. 96% in our cohort).…”
Section: Discussionmentioning
confidence: 69%
“…Our group 33 and others [34][35][36] recently reported a higher prevalence of AT1R-Ab in pediatric versus adult kidney transplant recipients, highlighting potentially important differences between these 2 populations with respect to the development of non-HLA antibodies. In particular, pediatric kidney transplant patients appear to have a higher rate of de novo AT1R-Ab formation.…”
mentioning
confidence: 64%
“…Levels of AT 1 R antibodies have been found associated with the age of the patient. The median AT 1 R antibody level has already reached the saturated level of the assay in stable paediatric transplant patients, which is significantly higher than in the adult transplant group and the control non‐transplant group (Bjerre et al., 2016). This result suggests that the interpretation of AT 1 R test results may need to consider all confounding factors.…”
Section: Antibodies Against Angiotensin II Type 1 Receptor (At1r)mentioning
confidence: 98%
“…The presence of these non‐HLA antibodies does not always cause graft dysfunction. It has been reported that AT 1 R antibodies caused acute rejection in two paediatric kidney transplant cases, while some paediatric kidney transplant recipients who had high levels of AT 1 R antibodies had normal graft function (Pearl et al., 2015) (Bjerre et al., 2016). The precise role of these non‐HLA antibodies in graft rejection warrants further study.…”
Section: Mechanism Of Stimulation Of Non‐hla Antibodiesmentioning
confidence: 99%
“…Angiography and embolization will be performed if intrarenal lesions are clinically significant. Hypertension, a common complication after rTX, occurs in 30%–50% of all kidney transplant recipients depending on the method of blood pressure measurement, definition, and normative data used . Up to 7% have uncontrolled hypertension with SBP greater than 95th percentile despite being on antihypertensive medications due to RAS.…”
Section: Long‐term Follow‐up Of Pediatric Renal Transplants (Figure )mentioning
confidence: 99%